Neglected Domestic Chore of Women and Its Health Impacts: An Exploratory Qualitative Study from Rural Maharashtra - Abhijeet V Jadhav (Medsci Publications, 2018)
Introduction: In underdeveloped rural areas most of the work is powered by human energy and women need to contribute a lot. There is literature gap regarding the effect of such streneous lifestyle on their health, especially on Musculo-Skeletal Disorders (MSDs). Methodology: It was an exploratory qualitative study in two villages with 29 women, through a pre-tested, semi-structured interview schedule. Results: Apart from contributing to farm activities, women have to work hard towards domestic work, fetching water, care of domestic animals, bringing fodder and firewood. Most of these are very streneous tasks but women ranked bringing fodder, firewood and water on the top-list of difficulty. There were many MSDs in this group and health-seeking was not effective due to lack of proper health care facilities. Discussion: The excessive burden of MSDs appears to be due to harsh domestic working conditions. Most of the streneous physical activities can be reduced if basic facilities like water and cooking gas connection are made available at door-step. There is a need for further scientific investigation of this problem and better implementation of rural programs towards access to water, cooking gas, fodder and health care to reduce the drudgery.